Effect of interval and continuous small-sided games training on the bio-motor abilities of young soccer players: a comparative study - Farhad Daryanoosh; Hossein Alishavandi; Javad Nemati; Aref Basereh; Alireza Jowhari; Enayatollah Asad-manesh; Rafael Oliveira; João Paulo Brito; Pablo Prieto-González; Tomás García-Calvo; Kayvan Khoramipour; Hadi Nobari (BMC, 2023)
Abstract Objective The present study compared the effects of two different small-sided game (SSG) training methods, interval (ISSG) and continuous (CSSG) on the bio-motor abilities of young soccer players. Methods Sixteen young soccer players (age: 19.5 ± 0.5 years; height: 177 ± 4.72 cm) were ranked based on the result of a running-based anaerobic sprint test (RAST) and randomly divided into two groups: CSSG (n = 8) and ISSG (n = 8). The training protocols were performed for eight weeks, three sessions per week. Participants were assessed twice (pre- and post-intervention) to estimate their anaerobic capacity with the RAST, aerobic capacity with Yo-Yo intermittent recovery test, body fat percentage with a bioimpedance analysis, speed with a 30-meter run test, and agility with the Illinois agility test. During the training session, the rating of the perceived exertion (RPE) and heart rate (mean and maximum) were recorded to assess the training load. Results In general, aerobic and anaerobic capacities improved after ISSG (p < 0.05, for all). The between-group analysis with repeated measures ANOVA revealed higher values for ISSG than CSSG groups post-intervention in anaerobic power (p = 0.042, ηp2 = 0.264). In addition, the independent t-test results indicated that ISSG presented lower values of mean heart rate (p = 0.023, effect size [ES] = 0.85) and RPE (p < 0.05, ES = 0.88) than CSSG. Moreover, higher values for maximum heart rate were revealed for ISSG than for the CSSG group (p = 0.004, ES = 0.85). Conclusion In conclusion, the findings of this study suggests that ISSG can lead to better improvements in anaerobic power and aerobic capacity than CSSG. Additionally, the ISSG led to a lower mean heart rate and RPE than the CSSG. Therefore, coaches and trainers may want to consider incorporating ISSG into their training programs for young soccer players to enhance their bio-motor abilities.